Role of plasma membrane transporters (N+/H+ and HCO3-) in mediating mammalian longitudinal bone growth and fracture healing - Abdul, Abubakar Adamu (2016)
Mammalian long bone growth and secondary bone healing occur by means of endochondral ossification, which involves tightly controlled cellular differentiation of chondrocytes at the epiphyseal region and callus formation at the fracture site. Although the cellular mechanism of chondrocyte differentiation that regulates long bone growth and fracture healing is still poorly understood, plasma membrane transporters were thought to have the mediating roles. This study aimed to investigate the roles of Na+/H+ antiporter (NHE1) and HCO3- anion exchanger 2 (AE2) in linear bone growth and secondary fracture healing. The specific objectives were: (1) To study postnatal ex vivo rat model for longitudinal bone growth investigations. (2) To investigate the role of Na+/H+ (NHE1) and HCO3- (AE2) exchange across membrane of chondrocytes in mammalian longitudinal bone growth. (3) To investigate the effect of recombinant human growth hormone (rhGH) on the localisation of NHE1 and AE2 membrane transporters on long bone growth in rat. (4) To establish metatarsal fracture model in rats for in vivo investigation of secondary bone healing. (5) To investigate the role of NHE1 (Na+/H+) and AE2 (HCO3-) membrane proteins during secondary bone healing in rat. Firstly, an experiment was undertaken to determine the suitable age to study bone growth using rat pups ex vivo model. The result showed direct bone sectioning for histology was possible across all age groups in metatarsal bone rudiments and in 7-13 day-old pups tibia. However, tibial sectioning was relatively difficult in 14 and 15 day-old rats. Significant differences in tibia and metatarsal growth plate (GP) length was observed among different age groups at different incubation periods (P<0.05). Significant differences of chondrocyte densities in the GP of tibia and metatarsal were recorded before and after 72 hrs incubation. Ex vivo longitudinal growth of tibia and metatarsal bone of rats at age of 7-15 day-old was possible under conducive physiological condition and maximum growth rate was observed in tibia of 10 day-old rats (P10). Postnatal (P10) metatarsal and tibial bones were cultured for 48 hrs ex vivo in the presence of plasma membrane inhibitors of 5-ethylisopropyl amiloride (EIPA) and 4,4’-diisothiocyano-2,2”-stilbenedisulfonic acid (DIDS) for NHE1 and AE2 respectively. The study revealed bone growth suppression by approximately 11% at concentration of 444 μM and 250 μM of EIPA and DIDS respectively. The two inhibitors had no significant effect on the total GP length but significantly affect the total GP and HCZ chondrocytes densities. There was no significant difference between NHE1 and AE2 localisation and fluorescence signaling across GP length. The remarkable suppression of bone growth along with the inhibition of chondrocytes proliferation at the entire GP and HCZ by EIPA and DIDS was an indication that the plasma membrane proteins (NHE1 and AE2) have potential role in bone growth through regulation of chondrocytes density. In order to determine whether there is effect of bone growth inhibition by EIPA and DIDS on bone growth stimulation under the influence of growth hormone (GH), P10 rat metatarsal and tibia were cultured for 48 hrs in the presence of GH in combination with EIPA, DIDS or the vehicle, DMSO (control). Results showed bone cultured in DMSO recorded steady growth similar as treatment with additional GH. In the presence of GH fluorescence labeling of NHE1 and AE2 membrane proteins along GP was enhanced along with increased in the longitudinal bone growth. However, the combination of GH with EIPA or DIDS suppressed longitudinal bone growth, total GP length, GP chondrocytes density and localisation of NHE1 and AE2 along the GP. The fluorescence labeling of NHE1 and AE2 were also significantly inhibited in EIPA+GH or DIDS+GH treatments. The present study also established a reproducible transverse mid shaft 3rd metatarsal fracture model for laboratory investigations. The model produced a fracture at the shaft of metatarsal bones that was 100 % transverse, 73% located at mid shaft with minimal fracture angulations based on radiographic evidence (0.48 ± 0.09O at anterior posterior view; 0.78 ± 0.17O at lateral view). There was minimal soft tissue injury, no infection or delayed bone union observed. Varying degree of weight bearing lameness was initially observed but subsequently absent at day six onwards post-surgery. Callus index was observed to peak in week 2 and 3 (2.02 ± 0.1 and 1.99 ± 0.13, respectively) but declined to 1.10 ± 0.04 in week 7 during consolidation period. There was no significant difference between the histological and radiographic healing scores at week 7 post-surgery. Chondrocytes in fracture callus could be detected as early as first week of bone healing, which peaked after 3 weeks and subsequently declined and ceased at week 6. NHE1 and AE2 localisation was recorded throughout the period of healing but peak signaling was recorded in the first 4 weeks of healing and then significantly declined from week 5 onwards to week 7. The NHE1 localisation was significantly higher than that of AE2 during the healing score between NHE1 and AE2. In conclusion, EIPA and DIDS have significantly inhibited longitudinal bone growth, HCZ length and total GP chondrocyte density. Expression of NHE1 and AE2 was affected by the inhibition of EIPA and DIDS in the presence of GH. The transporters were also found to be present in the fracture site at significant high level throughout the first 4 weeks of fracture healing period. This result suggested the possible role of NHE1 and AE2 in longitudinal bone growth as well secondary fracture healing.